The Availability of Academic Journals in Africa - Harle, Jonathan (International Higher Education, 2011)
Research requires a good flow of the latest scholarly informationbooks, journals, dataand sub-Saharan universities have long faced particular challenges in Africa. But the past decade has shown considerable efforts to address this information gap. In fact, a study published by the Association of Commonwealth Universities last year suggests that the picture may actually be much brighter than is often assumed.